Avalanche breakdown in multicrystalline solar cells due to preferred phosphorous diffusion at extended defects. (2nd June 2012) - Bauer, Jan; Lausch, Dominik; Blumtritt, Horst; Zakharov, Nikolai; Breitenstein, Otwin
ABSTRACT: Multicrystalline solar cells break down strongly at reverse voltages well below the theoretical limit. Previous explanations were based on assuming a constant depth of the junction below the surface. In this work, preferred phosphorous diffusion at special line defects in grain boundaries is shown to lead to spikes in the p–n junctions even below flat surfaces. The curvature radii of the spherical p–n junction bending are measured by electron beam‐induced current to be in the range of 300–500 nm, leading to the observed type III avalanche breakdown voltages. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Avalanche pre‐breakdown in multicrystalline solar cells is found to be due to submicron‐sized nearly spherical dents in the p–n junction. These dents are assumed to be caused by enhanced diffusion of phosphorous during emitter formation at special crystallographic line defects. In spite of a flat solar cell surface, this phenomenon leads to pre‐breakdown due to locally enhanced electric fields even in alkaline textured solar cells, which normally exhibit a flatter surface than acidic textured ones.